Biomechanical analysis into backstroke start kinematics: The influence of a backstroke start device - Budzynski-Seymour, E.; Steele, J.; Langdown, L.; Jessop, D. (SportRxiv, 2019)
Background: Backstroke starts have received little scientific attention; this may be due to the ongoing modifications to rules but also the fact that the majority of swim starts occur from a dive. As such, this has been the focus for much swim start research. Backstrokers face the problem of slipping from the wall which is a reasonably common mishap and has serious consequences for the competitor. FINA approved the use of a new backstroke start ledge to help avoid this mishap and therefore the aim of the study was to investigate what advantages come from using this ledge (L) over the wall (W). Methods: Twelve well trained male and female competitive swimmers took part in the study and completed six maximum effort sprints; three under each condition. Results: The results showed significantly greater flight distance (L = 4.22m±0.42, W = 4.06m±0.35, p<0.05) and peak hip height during the flight phase (L = 0.39m±0.15, W = 0.20m±0.14, p<0.01) when using the ledge. Discussion: It was concluded therefore that the ledge positively effects backstroke start performance during the flight phase of the start.